2017
DOI: 10.1177/1357633x17717601
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes following telestroke-assisted thrombolysis for stroke in Ontario, Canada

Abstract: Introduction Since 2002, the Ontario Telestroke Program has provided hospitals in under-served regions of the province the opportunity to offer intravenous thrombolysis with tissue plasminogen activator (IV tPA) to eligible patients. The purpose of this study was to determine whether telestroke-assisted IV tPA patients had similar risks of 7- and 90-day mortality, symptomatic intracerebral haemorrhage (sICH), and poor functional outcome compared to patients who received IV tPA with on-site expertise. Methods D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…Functional outcomes were similar whether the patient was treated in a stroke telemedicine hospital (spoke) or in a stroke centre hospital (hub) . Similar findings have been reported in the US and Canada . In a meta‐analysis of 26 studies (6605 patients receiving thrombolysis), no significant differences were found between stroke telemedicine and control groups in terms of in‐hospital mortality, 90‐day mortality, symptomatic intracranial haemorrhage, and clinical outcome at discharge or at 90‐day follow‐up …”
Section: Discussionsupporting
confidence: 75%
“…Functional outcomes were similar whether the patient was treated in a stroke telemedicine hospital (spoke) or in a stroke centre hospital (hub) . Similar findings have been reported in the US and Canada . In a meta‐analysis of 26 studies (6605 patients receiving thrombolysis), no significant differences were found between stroke telemedicine and control groups in terms of in‐hospital mortality, 90‐day mortality, symptomatic intracranial haemorrhage, and clinical outcome at discharge or at 90‐day follow‐up …”
Section: Discussionsupporting
confidence: 75%
“…3 Acute stroke care at remote hospitals throughout the province of Ontario (population 14 million) is supported by the Ontario telestroke program (OTP). 4 Currently, there are 31 hospitals that refer to the OTP, including designated district stroke centers (primary stroke centers) and nondesignated hospitals that provide thrombolytic therapy. Emergency physicians at these referring hospitals request a telestroke consultation by calling CritiCall, a provincial program that supports access to emergent care.…”
mentioning
confidence: 99%
“…15,16 Over the past decade, telemedicine-guided acute ischaemic stroke care has been shown to be accurate and safe and to produce comparable favourable clinical outcomes compared to traditional on-site care. 1722 There is also growing evidence that telemedicine is effective in improving the rate and timeliness of tPA administration. 2326…”
Section: Introductionmentioning
confidence: 99%
“…While telemedicine models have been broadly used in ED stroke care, most prior studies have been limited in scope to a single network. 15,1726 In order to characterise the overall impact of telemedicine better, we studied emergency stroke care in four telemedicine networks. The objectives of this study were to (a) identify the overall impact of telemedicine on ED stroke care measures of time to interpret a computed tomography (CT) of the head and time to administer tPA, (b) identify if the impact of telemedicine varied by network and (c) describe the variation in these process outcomes by telemedicine across EDs.…”
Section: Introductionmentioning
confidence: 99%